Peluang Pengembangan Manajemen Badan Usaha Milik Desa (BUMDES) Berbasis Ekonomi Syariah sebagai Solusi Pembangunan Desa yang Berkeadilan - Mila Sastika; Chuzaimah Batubara (Universitas Muhammadiyah Enrekang, 2023)
Sustainable and equitable rural development can be achieved by integrating the principles of Islamic economics into the management of Village-Owned Enterprises (BUMDES). This study analyzes the opportunities for developing Shariah-based management of BUMDES as a solution for equitable rural development. A qualitative approach was used, with data collected through in-depth interviews and literature review. The research findings indicate that the development of Shariah-based BUMDES can serve as a solution to achieve sustainable and equitable rural development. The management of Shariah-based BUMDES involves the application of Islamic economic principles, such as social justice, community involvement, and avoidance of usury. The study concludes that the development of Shariah-based BUMDES management is a relevant and effective solution in promoting equitable rural development. The implementation of Islamic economic principles in the management of BUMDES can have a positive impact on the welfare of rural communities, create opportunities for fair economic participation, and improve the quality of life for rural residents.